Protective Effects of Sweet Orange Peel (Citrus Sinensis L.) The Induction of Micronuclei Induced by Cyclophosphamide in Human Peripheral Lymphocytes - Al –Taai, Ekhlas Mohammed F (Journal of Food Technology Research, 2016)
Recycling of fruit waste is one of the most important ways of utilizing it in a number of novel products , as well as in medicine, so came this research to verify the protective role of the extracts of sweet orange (Citrus sinensis L.) peels against genotoxicity induced by cyclophosphamide on human peripheral lymphocytes using the micronucleus and chromosomal aberration tests. Conducted overlap between Aqueous and alcohol extracts orange peel with the drug, through three types of transactions (before, after, with treatment). In order to test the effectiveness of the extracts, three concentrations of 5, 10 and 15 µg / ml where tested the prevention or minimization the effect of the drug (80 µg / ml) on human blood lymph . The extracts of the orange peel has antimutagenic potential induced by cyclophosphamide this may prevent the mutagenic effect of various genotoxic or carcinogenic agents, and thus utilization of fruit waste and products for therapeutic purpose.